Оценка эффективности утилизации вторичных энергоресурсов в электрохимических энергоустановках транспортных судов - Горбов, Виктор Михайлович; Митенкова, Вера Сергеевна; Карпов, Максим Александрович; Федорова, Ольга Павловна (НТУ "ХПИ", 2016)
Проведен анализ и выполнена оценка эффективности утилизации вторичных энергоресурсов в судовых электрохимических энергетических установках на базе твёрдотопливных топливных элементов. Получены значения потенциально возможного количества энергетических ресурсов для обеспечения общесудовых потребностей, которые можно получить путем утилизации пара или горячей воды на выходе из топливных элементов. Представлены рекомендации по целесообразности использования различных утилизационных схем в судовых электрохимических установках.

Analysis of waste energy utilization efficiency in electrochemical power plants based on proton exchange membrane fuel cells for transport vessels is done in this article. Quantitative estimation of waste heat energy flow in electrochemical power plants from 100 kW to 2000 kW operated on pure hydrogen is the main aim of research. Usage of hot water or saturated (or slightly superheated) steam at outlet from fuel cell as heating agent is considered. Total fuel mass and capacity for one-way trip are estimated for electrochemical power plants operated on pure hydrogen, methanol and liquefied natural gas. Potentially-enable quantity of power resources obtained through utilization of heat power and slightly superheated steam is come out. Analysis of these indexes makes possible justification of rational engineering choices at ships’ conceptual design and elaborates recommendations of keeping options for different variants of waste energy utilization in electrochemical power plants based on low-temperature fuel cells.
Estimation of waste energy utilization efficiency in electrochemical power plants of transport vessels
Keywords: электрохимический генератор; утилизационная паровая турбина; судовая опреснительная установка; система водяного отопления; обработка балластных вод.; electrochemical generator; ship desalination plant; water heating system; heat generator